The Persistence of Social Power in Post-Catholic Ireland: A New Historicist Study of Sally Rooney's Normal People - Husein Asadus Shahra; Karina Hanum Luthfia (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
This study aims to examine how social power persists in post-Catholic Ireland as represented in Sally Rooney's Normal People (2018). Set against the backdrop of Ireland’s transition from a society strongly influenced by Catholic authority to a more liberal and secular social order, the novel reveals that the decline of religious influence does not necessarily eliminate mechanisms of social control. Using a qualitative descriptive method and Stephen Greenblatt’s New Historicist approach, this study analyzes how experiences of silence and shame function as manifestations of social power within contemporary Irish society. The findings indicate that power no longer operates primarily through religious institutions but through family structures, class hierarchies, educational environments, and cultural norms that shape individual behaviour and self-perception. These mechanisms are represented through the experiences of Marianne Sheridan and Connell Waldron, whose lives reflect the continuing influence of social regulation in post-Catholic Ireland. This study argues that secularization in Ireland has transformed rather than eliminated social control, revealing a gap between the image of a progressive society and the persistence of power relations in everyday life.